2012
DOI: 10.1021/ie3014428
|View full text |Cite
|
Sign up to set email alerts
|

Attrition Studies of an Iron Fischer–Tropsch Catalyst Used in a Pilot-Scale Stirred Tank Slurry Reactor

Abstract: Attrition resistance is a key design parameter for catalysts used in slurry phase Fischer–Tropsch (F–T) reactors, especially for industrial-scale reaction. It is well-known that iron F–T catalyst particles undergo physical attrition and chemical stresses caused by phase transformations. Here we report on attrition properties of a Fe–Cu–K–SiO2 catalyst used in a pilot-scale stirred tank slurry reactor (STSR) under low temperature F–T reaction conditions. The wax-free catalysts were characterized by SEM, EDS, BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…Attrition has been studied for many materials at room temperature, e.g., Fischer-Tropsch catalyst [19][20][21][22][23][24], coal [25,26], glass [27], oxygen carriers [3,[28][29][30], and various crystals [31][32][33]. Lin et al [21] and Bukur et al [20,22] carried out the attrition tests of an iron Fischer-Tropsch (F-T) catalyst in a stirred-tank slurry reactor. They concluded that attrition of the F-T catalyst was induced by both the mechanical stress from particles' collisions and the chemical stress due to phase transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Attrition has been studied for many materials at room temperature, e.g., Fischer-Tropsch catalyst [19][20][21][22][23][24], coal [25,26], glass [27], oxygen carriers [3,[28][29][30], and various crystals [31][32][33]. Lin et al [21] and Bukur et al [20,22] carried out the attrition tests of an iron Fischer-Tropsch (F-T) catalyst in a stirred-tank slurry reactor. They concluded that attrition of the F-T catalyst was induced by both the mechanical stress from particles' collisions and the chemical stress due to phase transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Physical stability issues on the other hand are mainly comprised of attrition and abrasion of catalyst pellets, especially for stirred reactors. 87 Such attrition or abrasion of the catalyst could ultimately pollute the remaining carbohydrate pulp with catalyst particles, hindering further analysis and pulp valorization. Future research should focus on maximizing the catalyst impact resistance, for instance by exploring more stable catalyst 88 supports, like niobia 89 or carbon nitrides.…”
Section: ■ Fundamental Research Questionsmentioning
confidence: 99%
“…However, more pronounced catalyst deactivation requires continuous addition, removal, and regeneration of the catalyst, for example, with slurry bubble column reactors. , The optimization of said regeneration processes for RCF purposes has not yet been tackled by the community and is ideally coupled with extensive catalyst deactivation studies, in close collaboration with the catalyst manufacturers. Physical stability issues on the other hand are mainly comprised of attrition and abrasion of catalyst pellets, especially for stirred reactors . Such attrition or abrasion of the catalyst could ultimately pollute the remaining carbohydrate pulp with catalyst particles, hindering further analysis and pulp valorization.…”
Section: Fundamental Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the incompatibility in such reaction systems, especially for biphasic reactions involving solid catalysts, vigorous stirring is required to ensure suspension of solid catalyst particles and sufficient mixing of reactants, mitigating mass‐transport resistance 2. However, such vigorous stirring not only requires a large energy input, but causes fragmentation of catalyst particles because of repeated collisions and persistent abrasion, also 3. Recently developed microfluidic and micromixing technologies open a promising avenue towards stirring‐free reactions by enforcing continuous contact between immiscible reactants and catalysts in micrometer‐sized spaces 4.…”
Section: Epoxidation Of Allylic Alcohols In (A) a Static Pickering Emmentioning
confidence: 99%